Polygonatum binatifolium, a new species of Polygonatum (Asparagaceae) from Guizhou, China - Zhu, Heng-Xing; Huang, Fei-Yi; Chen, Hong-Yuan; Zhang, Hong-Jing; Dai, Qian-Li; Yi, Si-Rong (Phytotaxa, 2022)
Polygonatum binatifolium, from Guizhou, China, is newly described and illustrated. The new species is morphologically most similar to P. cyrtonema in sharing an erect stem, pendulous flowers, glabrous peduncles and pedicels, campanulate, yellowish green perianths, and glabrous, included stamens, but differs by its shorter stems (20–50 cm vs. 50–100 cm), fewer leaves (5–9 vs. 10–15) of which the lowermost two being opposite, fewer flowers (up to 5 vs. up to 14), shorter peduncles (2–5 mm vs. 1–6 cm), shorter filaments (ca. 1.0 mm vs. 3–4 mm) and anthers (1.6–1.9 mm vs. 3.5–4.0 mm), smaller ovary (1.8–2.2 mm vs. 3.0–6.0 mm) and shorter styles (1.5–2.0 mm vs. 1.2–1.5 cm), and smaller berries (5.5–6.5 mm vs. 6–12 mm) and seeds (2.4–3.0 × 2.0–2.4 mm vs. 3.8–5.6 × 2.8–3.6 mm). The species can be categorized as Critically Endangered (CR).